Venous Air Embolism Activates Complement C3 Without Corresponding C5 Activation and Trigger Thromboinflammation in Pigs - Storm, Benjamin S.; Ludviksen, Judith K.; Christiansen, Dorte; Fure, Hilde; Pettersen, Kristin; Landsem, Anne; Nilsen, Bent Aksel; Dybwik, Knut; Braaten, Tonje; Nielsen, Erik W.; Mollnes, Tom E. (Frontiers in Immunology, 2022)
Introduction: Air embolism may complicate invasive medical procedures. Bubbles trigger complement C3-mediated cytokine release, coagulation, and platelet activation in vitro in human whole blood. Since these findings have not been verified in vivo, we aimed to examine the effects of air embolism in pigs on thromboinflammation. Methods: Forty-five landrace pigs, average 17 kg (range 8.5-30), underwent intravenous air infusion for 300 or 360 minutes (n=29) or served as sham (n=14). Fourteen pigs were excluded due to e.g. infections or persistent foramen ovale. Blood was analyzed for white blood cells (WBC), complement activation (C3a and terminal C5b-9 complement complex [TCC]), cytokines, and hemostatic parameters including thrombin-antithrombin (TAT) using immunoassays and rotational thromboelastometry (ROTEM). Lung tissue was analyzed for complement and cytokines using qPCR and immunoassays. Results are presented as medians with interquartile range. Results: In 24 pigs receiving air infusion, WBC increased from 17×109/L (10-24) to 28 (16 42) (p<0.001). C3a increased from 21 ng/mL (15-46) to 67 (39-84) (p<0.001), whereas TCC increased only modestly (p=0.02). TAT increased from 35 µg/mL (28-42) to 51 (38 89) (p=0.002). ROTEM changed during first 120 minutes: Clotting time decreased from 613 seconds (531-677) to 538 (399-620) (p=0.006), clot formation time decreased from 161 seconds (122 195) to 124 (83-162) (p=0.02) and ⍺-angle increased from 62 degrees (57 68) to 68 (62-74) (p=0.02). In lungs from pigs receiving air compared to sham animals, C3a was 34 ng/mL (14-50) versus 4.1 (2.4-5.7) (p<0.001), whereas TCC was 0.3 CAU/mL (0.2-0.3) versus 0.2 (0.1-0.2) (p=0.02). Lung cytokines in pigs receiving air compared to sham animals were: IL-1β 302 pg/mL (190-437) versus 107 (66-120), IL-6 644 pg/mL (358-1094) versus 25 (23-30), IL-8 203 pg/mL (81-377) versus 21 (20-35), and TNF 113 pg/mL (96-147) versus 16 (13-22) (all p<0.001). Cytokine mRNA in lung tissue from pigs receiving air compared to sham animals increased 12-fold for IL 1β, 121-fold for IL 6, and 17 fold for IL 8 (all p<0.001). Conclusion: Venous air embolism in pigs activated C3 without a corresponding C5 activation and triggered thromboinflammation, consistent with a C3-dependent mechanism. C3-inhibition might represent a therapeutic approach to attenuate this response.